Innovative development of agriculture is the basis of UPC moder (Journal of Economic Research & Business Administration, 2018)
The paper considers the modernization of the agro-food complex, which assumes the acceleration of the rates of structural and technological modernization of the production potential of the agroindustrial complex and the creation of conditions for the realization of the potential. The problem of activation of innovative activity in the implementation of tasks and mechanisms for supporting innovative programs and projects determined by the state innovation policy is considered. The main task of this task is to mobilize the scientific and technical potential of the industry for technical and technological renewal of domestic agriculture. Areas for improving the organization of innovative activities in agriculture are identified. It is emphasized that the formation of a mechanism for stimulating innovative modernizationof agriculture is determined by the creation of a competitive sector of research and development and theconditions for its resource reproduction; creation of an effective system of innovative modernization ofagriculture. The development of innovative processes in the development of innovative achievements isconsidered, which will contribute to the creation of conditions for effective management of agro-industrialproduction. The experience of the policy of modern innovation activity in the regions is reflectedin the work; examples are given in the framework of implementing the policy of innovative development– the activity of a large multi-profile holding Bayserke-Agro (Almaty region), where the main fieldof activity is cattle breeding, the subsequent processing of dairy products holding the direction of theseworks is robotized. The experience of creating various innovative and innovative consulting centers isconsidered – the special park «Innovative Technologies Park», the activity of innovation centers such asthe «Innovation Quality Center», created with the aim of developing in Kazakhstan the preparation ofbusiness entities for the implementation and certification of management systems or an integrated systemManagement on the basis of national and international standards ISO and OHSAS.